The Wife of Bath in afterlife : ballads to Blake - Bowden, Betsy (Studies in text and print culture., 2017)
"This study investigates interpretation of a late-fourteenth-century fictional character in both verbal and visual art of the period 1660-1810. Audiovisual analysis and diachronic afterlife studies intertwine concerning the Wife of Bath in songs, scholarship, commentary, poetic paraphrases, musical theater in London and on the Continent, paintings, and book illustration"--